Damage Identification by the Static Virtual Distortion Method - Kołakowski, P. (Engineering Transactions, 2004)
This paper describes the application of a structural reanalysis technique called the Virtual Distortion Method, coupled with an optimisation technique called the Gradient Projection Method, to the damage identification problem for the case of the static structural analysis. The outline of the Virtual Distortion Method is provided and the fundamentals of the Gradient Projection Method are explained. Subsequently the damage identification problem for the static load case is posed. Numerical example of a truss structure is demonstrated. Conclusions are presented with the emphasis on advantages of the employed methods in numerical computations.